PENGARUH PENDIDIKAN KESEHATAN TERHADAP KEPATUHAN DIET PADA PASIEN DIABETES MELLITUS TIPE-II DI PUSKESMAS TAMIANG HULU KABUPATEN ACEH TAMIANG - Zulkarnaini Zulkarnaini; Nora Hayani; Azwarni Azwarni; Keumalahayati Keumalahayati (Jurnal Ilmiah Hospitality, 2022)
The latest estimate of the International Diabetes Federation (IDF), there are 382 million people living with diabetes in the world in 2013. In 2035 this number is expected to increase to 592 million people. Diabetes mellitus arises because of heredity and behavior. It can be said that hereditary factors are slow while those with diabetes mellitus are now a reflection of lifestyle changes including a diabetic diet. The main obstacle in handling diabetic mellitus is the saturation of patients in taking diet therapy which is very necessary to achieve success. This study aims to determine the effect of health education on dietary compliance in patients with type-II diabetes mellitus at the Tamiang Hulu Health Center in Aceh Tamiang District in 2019. The design of this study used quasi-experimental design with one group pretest-posttest. This study uses primary data collected using a questionnaire. The number of samples in this study were 15 respondents with probability sampling techniques (purposive sampling). The results of this study indicate that of the 15 majority respondents who did not adhere to the diet as many as 13 (86.7%) respondents and after being given the majority health education obediently carried out a diet of 10 (66.7%) respondents. The results of this study also concluded that there was an effect of health education on adherence to diet type-II diabetes mellitus at the Tamiang Hulu Health Center in Aceh Tamiang District with a p-value of 0,000 (p <0.05). The researcher suggested that respondents maintain a good diet and run a good diet and regulate the eating behavior.